2008
DOI: 10.1002/ca.20679
|View full text |Cite
|
Sign up to set email alerts
|

A human case of an azygos lobe: Determining an anatomical basis for its therapeutic postural drainage

Abstract: An azygos lobe of the human lung is one of the most common lung malformations. However, there are only a few anatomical reports concerning the bronchial and blood supply to this lobe. We encountered the azygos lobe in an anatomical dissection course. The azygos lobe of this case was examined macroscopically and lung parenchyma, including alveoli, terminal bronchioles, and bronchial arteries and veins, was partially removed under a stereoscopic microscope. The azygos lobe was situated medial to the superior lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The azygos lobe is a congenital variant with an incidence of about 0.4-1.2% of the population [2]. It occurs when the azygos vein pen- …”
Section: Discussionmentioning
confidence: 99%
“…The azygos lobe is a congenital variant with an incidence of about 0.4-1.2% of the population [2]. It occurs when the azygos vein pen- …”
Section: Discussionmentioning
confidence: 99%
“…In our article (Arakawa et al, 2008), we stated that our study is the third report of its kind involving Japanese individuals. As suggested by Dr. Das, Kobayashi et al (1995) reported a case of right human azygos lobe in the Kagawa Medical School.…”
mentioning
confidence: 85%
“…Our report of the human azygos lobe (Arakawa et al, 2008) described the anatomical detail of the branching pattern of the bronchus, pulmonary arteries, and veins. Our article focused the bronchial branching patterns to determine the better procedure of the therapeutic postural drainage for the patient with the azygos lobe, and therefore, we did not represent these dimensions in our article.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The azygous lobe is a normal anatomical variant with reported incidence of 0.2–1.2% (1). We report a case of a 51-year-old man with past medical history significant for drug and alcohol abuse, who presented to the emergency department with altered mental status and hypoxic respiratory failure.…”
mentioning
confidence: 99%